Is the Volatility of the Islamic Stock Index Lower than the Conventional Stock Index during Covid-19 Pandemic? Empirical Evidence in Indonesia Stock Exchange - Purwanto Widodo (Universitas Pembangunan Nasional Veteran Jakarta, 2022)
AbstractThe Islamic stock index is a composite index of Islamic stocks listed on the Indonesia Stock Exchange (IDX). Therefore, is expected to have low volatility and be resistant to a possible financial crisis. This study aims to see whether the volatility of the Islamic stock index is lower than the conventional stock index during the Covid-19 crisis. The data taken is daily stock closing data for JKSE and JII for the period March 1, 2020, to April 30, 2022, with a total of 532 observations. The model used is ARMA/ ARIMA which is then followed by the ARCH – GARCH volatility model. The results of this study indicate that the appropriate Islamic and conventional stock index volatility model is GARCH(1,1) and there is no problem with the asymmetry effect. The findings of this study are that during the Covid-19 crisis, there was a tendency that the return volatility of the Islamic stock index to be lower than conventional and that the Islamic and conventional stock indexes were relatively low against the financial crisis that occurred. AbstrakIndeks saham syariah adalah indeks komposit saham syariah yang tercatat di Bursa Efek Indonesia (BEI). Karena itu, diharapkan memiliki volatilitas rendah dan tahan terhadap krisis keuangan yang kemungkinan terjadi. Penelitian ini, bertujuan untuk melihat apakah volatilitas indeks saham syariah lebih rendah dibandingkan indeks saham konvensional semasa krisis yaitu Covid-19. Data yang diambil adalah data penutupan saham harian JII dan IHSG periode 1 Maret 2020 sampai dengan periode 30 April 2022, sebanyak 532 pengamatan. Model yang dipergunakan adalah ARMA/ ARIMA yang kemudian dilanjutkan dengan model volatilitas ARCH – GARCH. Hasil penelitian ini menunjukkan bahwa model volatilitas indeks saham syariah maupun konvensional yang sesuai adalah GARCH(1,1) dan tidak terdapat masalah effect asimetri. Temuan penelitian ini adalah selama krisis Covid-19 terdapat kecenderungan bahwa volatilitas return indeks saham syariah lebih rendah dibandingkan konvensional dan indeks saham syariah maupun konvensional relative tidak imum terhadap krisis keuangan yang terjadi.